2018
DOI: 10.1101/494237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental Dieldrin Exposure Alters DNA Methylation at Genes Related to Dopaminergic Neuron Development and Parkinson’s Disease in Mouse Midbrain

Abstract: Human and animal studies have shown that exposure to the organochlorine pesticide dieldrin is associated with increased risk of Parkinson's disease (PD). Despite previous work showing a link between developmental dieldrin exposure and increased neuronal susceptibility to MPTP toxicity in male C57BL/6 mice, the mechanism mediating this effect has not been identified. Here, we tested the hypothesis that developmental exposure to dieldrin increases neuronal susceptibility via genome-wide changes in DNA methylatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…[61][62][63] In a previous animal model study, we showed that developmental exposure to the organochlorine pesticide dieldrin, which is known to be associated with increased PD risk, led to sex-specific hypermethylation in the Nr4a2 gene body in female mice. 64 These previous results, along with our present data, suggest that sexspecific epigenetic regulation at the NR4A2 gene may play a role in idiopathic PD risk.…”
Section: Male-specific Pd-associated Changes In Dna Methylation At Nr4a2supporting
confidence: 87%
See 1 more Smart Citation
“…[61][62][63] In a previous animal model study, we showed that developmental exposure to the organochlorine pesticide dieldrin, which is known to be associated with increased PD risk, led to sex-specific hypermethylation in the Nr4a2 gene body in female mice. 64 These previous results, along with our present data, suggest that sexspecific epigenetic regulation at the NR4A2 gene may play a role in idiopathic PD risk.…”
Section: Male-specific Pd-associated Changes In Dna Methylation At Nr4a2supporting
confidence: 87%
“…One previous study found decreased expression of PTPRN2 in the SN of PD patients, while another found increased expression in DA neurons from PD patients with LRRK2 G2019S mutations. 73,74 Interestingly, given the known role of environmental exposures in PD and work in our lab investigating pesticide exposures and PD, 64,75 another study found an association between pesticide exposure and hypomethylation at a CpG in PTPRN2 in blood. 76 Taken together, our data adds to a growing collection of evidence supporting a role for epigenetic regulation of PTRPN2 in PD.…”
Section: Sex-specific Pd-associated Changes In Dna Methylation At Ptprn2mentioning
confidence: 96%
“…Pesticides can also target the SN. Dieldrin, an organochlorine pesticide, causes neurotoxic damage to the dopaminergic system [ 73 ]. Rotenone, an organophosphate, increases α-synuclein aggregation and inhibits mitochondrial complex I [ 74 ].…”
Section: Parkinson’smentioning
confidence: 99%
“…Beyond changes to DNA sequences, pesticides could affect gene expression epigenetically [ 131 , 132 ]. There is evidence that pesticide exposure is linked to alterations in DNA methylation [ 133 , 134 , 135 ]. Of particular relevance in this regard would be genes that encode proteins affecting AD etiology, such as that encoding Paraoxonase-1 (PON1) [ 136 , 137 ].…”
Section: Speculative Neuropathological Mechanisms Of Pesticidesmentioning
confidence: 99%